2018
DOI: 10.1371/journal.pntd.0006634
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory drug methotrexate used to treat patients with chronic inflammatory rheumatisms post-chikungunya does not impair the synovial antiviral and bone repair responses

Abstract: Chikungunya virus (CHIKV) is a mosquito-transmitted RNA alphavirus causing major outbreaks of infectious chronic inflammatory rheumatisms (CIR). Recently, methotrexate (MTX), a disease modifying anti-rheumatic drug has been used successfully to treat patients suffering from rheumatoid-like arthritis post-CHIK but its immunomodulatory activity in the context of viral persistence has been a matter of concerns. We herein used a model of primary human synovial fibroblasts (HSF) and the synthetic molecule polyriboi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
1
15
0
1
Order By: Relevance
“…Alternatively, instead of IFNγ expression by T H 1 cells, TNF expression by CD4 cells might have an important function in promoting chikungunya arthropathy 135 . TNF-expressing CD4 cells have a potential pathogenic function in psoriatic arthritis 143 and are targeted by methotrexate in RA 144,145 ; notably, methotrexate has shown some benefit in treating chikungunya 146,147 .…”
Section: Cd4 T Cells Chikv-specific Cd4 T Cells Have Beenmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, instead of IFNγ expression by T H 1 cells, TNF expression by CD4 cells might have an important function in promoting chikungunya arthropathy 135 . TNF-expressing CD4 cells have a potential pathogenic function in psoriatic arthritis 143 and are targeted by methotrexate in RA 144,145 ; notably, methotrexate has shown some benefit in treating chikungunya 146,147 .…”
Section: Cd4 T Cells Chikv-specific Cd4 T Cells Have Beenmentioning
confidence: 99%
“…Low-dose corticosteroids (with or without NSAIDs) seem to be effective in NSAID-refractory pat ients 35,113,146,171,175 , although the potential adverse effects of these drugs should be considered in risk-benefit assessments 31,176 . For patients with chronic chikungunya who are refractory to the aforementioned treatments, DMARDs have shown some efficacy 113,172 , and sulfasalazine and methotrexate have been suggested as first-line options 146,147 . However, chikungunya arthropathy is usually not overtly erosive 16,47 , and so DMARDs might seem hard to justify 177 unless an underlying destructive autoimmune disease is present.…”
Section: Treatments and Vaccines Anti-inflammatory Therapymentioning
confidence: 99%
“…MTX, a disease modifying anti-rheumatic drug (DMARD), is used clinically for rheumatoid or psoriatic arthritis and systemic lupus erythematosis with good therapeutic results [91] , [92] , [93] . It is a folic acid analogue that is either used as a monotherapy or in combination with other synthetic DMARDs.…”
Section: Drug Candidates Against Sars-cov-2 and Other Viral Diseasesmentioning
confidence: 99%
“…In addition to interfering with the synthesis of precursor nucleotides, MTX has been shown to exert an immunomodulatory role [91] . Recently, Municio et al [92] showed that long-term low-dose MTX treatment increased the expression of A20 in macrophages stimulated with TLR ligands or TNF-α ( Fig.…”
Section: Drug Candidates Against Sars-cov-2 and Other Viral Diseasesmentioning
confidence: 99%
“…A recent study revealed that MTX treatment is probably safe and does not affect the antiviral and inflammatory responses of primary human synovial fibroblasts (HSF). MTX alone did not increase the capacity of CHIKV to infect and replicate in HSF [82]. This fact is important because the immunomodulatory activity of MTX in the context of viral persistence has been of concern.…”
Section: Methotrexate Therapy Of Chronic Chikungunya Arthritismentioning
confidence: 99%